The mediation function of resting heart rate in how physical activity improves all-cause mortality: Continuous and automatic measurement via cardiac implantable electronic devices - Cheng, Chendi; Sun, Xue Rong; Chen, Keping; Hua, Wei; Su, Yangang; Xu, Wei; Wang, Fang; Fan, Xiaohan; Dai, Yan; Liu, Zhimin; Zhang, Shu (Frontiers in Cardiovascular Medicine, 2022)
Background Physical activity (PA) and resting heart rate (RHR) are connected with all-cause mortality. Moreover, there was an inverse correlation between PA and RHR.However, the causal relationship among PA, RHR, and long-term mortality has been rarely evaluated and quantified, particularly the mediation effect of RHR in the association between PA and all-cause mortality. Objective To describe the relationship between PA and RHR when consistently measured via cardiac implantable electronic devices (CIED) and further explore the mediation effect of PA on all-cause mortality through RHR. Methods Patients underwent CIED implantation and received remote home monitoring service were included. During the first 30–60 days after CIED implantation, daily PA and RHR were continuously measured and automatically transmitted by CIED. The primary endpoint was all-cause mortality. The multiple linear regression model was used to confirm the relationship between PA and RHR. The predictive values of both PA and RHR for all-cause mortality were assessed by multivariable Cox models. Causal mediation model was further established to verify and quantify the mediation effect of RHR in the association between PA and all-cause mortality. Results A total of 730 patients with CIED were included. The mean daily PA and RHR were 10.7 ± 5.7% and 61.3 ± 9.1 bpm, respectively. During a mean follow-up period of 55.8 months, 187(26.5%) death was observed. A negative linear relationship between PA and RHR was demonstrated in the multiple regression model (β = −0.260; 95% CI: −0.377 to −0.143, p < 0.001). Multivariable Cox proportional hazards analysis showed that both lower levels of PA (HR = 0.907; 95% CI: 0.878–0.936, p<0.001) and higher RHR (HR = 1.016; 95% CI: 1.001–1.032, P = 0.031) were independent risk factors of all-cause mortality. Causal mediation analysis further confirmed and quantified the mediation function of RHR in the process of PA improving all-cause mortality (mediation proportion = 3.9%; 95% CI: 0.2–10.0%, p = 0.036). Conclusion The effects of higher level of PA on improving life prognosis may be partially mediated through RHR among patients with CIED. It indicates that changes in the autonomic nervous function during postoperative rehabilitation exercises should get more attention.